Biexcitonic optical Stark effects in monolayer molybdenum diselenide. Issue 11 (November 2018) - Yong, Chaw-Keong; Horng, Jason; Shen, Yuxia; Cai, Hui; Wang, Alex; Yang, Chan-Shan; Lin, Chung-Kuan; Zhao, Shilong; Watanabe, Kenji; Taniguchi, Takashi; Tongay, Sefaattin; Wang, Feng
Abstract Floquet states, where a periodic optical field coherently drives electrons in solids1–3, can enable novel quantum states of matter4–6 . A prominent approach to realize Floquet states is based on the optical Stark effect. Previous studies on the optical Stark effect often treated the excited state in solids as free quasi-particles3, 7–12 . However, exciton–exciton interactions can be sizeably enhanced in low-dimensional systems and may lead to light–matter interactions that are qualitatively different from those in the non-interacting picture. Here we use monolayer molybdenum diselenide (MoSe2 ) as a model system to demonstrate that the driving optical field can couple a hierarchy of excitonic states, and the many-body inter-valley biexciton state plays a dominant role in the optical Stark effect. Specifically, the exciton–biexciton coupling in monolayer MoSe2 breaks down the valley selection rules based on the non-interacting exciton picture. The photon-dressed excitonic states exhibit an energy redshift, splitting or blueshift as the driving photon frequency varies below the exciton transition. We determine a binding energy of 21 meV for the inter-valley biexciton and a transition dipole moment of 9.3 debye for the exciton–biexciton transition. Our study reveals the crucial role of many-body effects in coherent light–matter interaction in atomically thin two-dimensional materials. Light–matter interactions in monolayer MoSe2 can be dramatically modified by the interactions between the excitonic states, leading to a rich set of light-driven coherent phenomena.